Lifetime enhancement of blue thermally activated delayed fluorescent devices by separated carrier channels using dibenzofuran-triazine type hosts - Kang, Yu Jin; Han, Si Hyun; Lee, Jun Yeob (Journal of industrial and engineering chemistry (Seoul, Korea), 2018)
[Display omitted] •Lifetime improvement of blue thermally activated delayed fluorescent devices by host engineering.•Electron transport type host materials derived from dibenzofuran-triazine.•Mixed host to separate carrier channel in blue thermally activated delayed fluorescent devices. Lifetime enhancement of blue thermally activated delayed fluorescent (TADF) devices was achieved using a carrier separating host structure which was developed using dibenzofuran-triazine type electron-transporting type host materials. Two host materials built on a chemical platform of dibenzofuran-triazine were synthesized as high triplet energy host materials for a blue TADF emitter and were mixed with a common hole-transporting type host. The separation of the carrier channel in the emitting layer lead to voltage reduction, external quantum efficiency increase, and lifetime extension of blue TADF devices.